PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PENDIDIKAN NONFORMAL DI DESA MATTANETE BUA KECAMATAN PALAKKA KABUPATEN BONE PROVINSI SULAWESI SELATAN - Gusnanda Bondan Febriansyah; Made Agus Adi; M. Vryatno Moonti (Jurnal Pallangga Praja (JPP), 2021)
This study aims to determine the empowerment of the poor through appropriate non-formal educationcarried out in Mattanete Bua Village, Palakka District, Bone Regency. Community empowermentis an effort to encourage motivation, increase public awareness of their potential to become realactions (Zubaedi 2007). Qualitative research approach, descriptive method and inductive approach.In qualitative research, the researcher assumes that by choosing this method, the researcher willfind informants in a broad and deep way. Informants from this study were the Head of PalakkaSubdistrict, Village Head, Village Secretary, Head of Dusun, and people who attended non-formaleducation. Data collection techniques using interview techniques, observation, documentationand field notes. Data analysis uses data reduction, data presentation and verification. The resultsof this study indicate that empowerment of the poor through non-formal education is carriedout by conducting anti-drug counseling, sewing skills training, and training on electric lightinginstallations. The implementation of empowerment of the poor through non-formal education thathas been implemented is appropriate in Mattanete Bua Village because it has succeeded in increasingthe knowledge and skills of villagers.